The value of water - Fehler Vallgårda, Amanda (2018)
Groundwater plays an essential role in the supply of fresh water around the world. Population growth and climate change might change how groundwater is used, managed and valued. This study looks at the total economic value of groundwater through a case study of the groundwater in the esker Uppsalaåsen. Two of the values – the use value and the value of groundwater of good quality – are monetised using the cost of production and the transfer method. It is also tested whether population growth and climate change are likely to affect the value of the groundwater. Population growth is found to have a positive correlation with the value of groundwater whereas the effect of climate change is limited. The use value is estimated to between 2.0 to 2.9 billion SEK and the value of groundwater of good quality to between 1.1 to 3.2 billion SEK. The total economic value of the groundwater is worth more. Several error terms shall however be kept in mind when interpreting the results.